The pivotal step of nanoparticle functionalization for the preparation of functional and magnetic hybrid opal films - Scheid, D.; Stock, D.; Winter, T.; Gutmann, Torsten; Dietz, C.; Gallei, M. (Journal of Materials Chemistry C)
The preparation of hierarchical and sophisticated particle architectures for mimicking structural colors known from nature still remains a challenge. In this study, the preparation of novel opal and double-inverse opal films based on thermally treated metallopolymer core particles with a silica shell is described. Thermal treatment leads to the formation of magnetic nanorattle-type particles. The main challenge of artificial particles is to ensure sufficient dispersibility after several synthetic steps. Especially silica particles providing surface hydroxyl groups tend to sinter at high temperatures leading to agglomeration. We present the introduction of trimethyl ethoxy silane (TMES) as an excellent functionalization reagent as the key reaction step. The necessity and success of functionalization are investigated by transmission electron microscopy (TEM) and zeta potential measurements. Importantly, solid state NMR techniques are employed to gain deeper insights into the chemical structure of the surface-attached reagent. Finally, by this convenient functionalization the preparation of elastomeric opal films and double-inverse opal films is proven successful revealing excellent optical film properties. Moreover, magnetic properties of these novel films are investigated by using magnetic force microscopy (MFM). The herein established route is expected to pave the way for the preparation of a variety of advanced and stimuli-responsive optical materials.
Keywords: Materials Science; silica; Physics; nmr; colloidal photonic crystals; light; polymerization; solids; structural color; thermo

Prior entry and temporal attention: Cueing affects order errors in RSVP. - Hilkenmeier, Frederic; Olivers, Christian N. L.; Scharlau, Ingrid (Journal of Experimental Psychology: Human Perception and Performance)
The law of prior entry states that attended objects come to consciousness more quickly than unattended ones. This has been well established in spatial cueing paradigms, where two task-relevant stimuli are presented near-simultaneously at two different locations. Here, we suggest that prior entry also plays a pivotal role in temporal attention paradigms, where stimuli appear at the same location but at distinct moments in time, in rapid serial presentation (RSVP). Specifically, we hypothesize that prior entry can explain temporal order reversals in reporting two targets from RSVP. In support of this, three experiments show that cueing attention toward either of the targets has a strong influence on order errors. We conclude that prior entry provides a viable explanation of the way in which relevant information is prioritized in RSVP. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: attentional blink; attentional enhancement; lag-1 sparing; prior entry; temporal cueing; visual attention; rapid serial presentation; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Female; Humans; Male; Neuropsychological Tests; Pattern Recognition; Visual; Time Factors; Visual Perception; Young Adult; Cues; Serial Recall; Visual Attention; Eyeblink Reflex

Prior entry explains order reversals in the attentional blink. - Olivers, Christian N. L.; Hilkenmeier, Frederic; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
When two targets are presented in rapid succession, the first target (T1) is usually identified, but the second target (T2) is often missed. A remarkable exception to this 'attentional blink' occurs when T2 immediately follows the first T1, at lag 1. It is then often spared but reported in the wrong order—that is, before T1. These order reversals have led to the hypothesis that 'lag 1 sparing' occurs because the two targets merge into a single episodic representation. Here, we report evidence consistent with an alternative theory: T2 receives more attention than T1, leading to prior entry into working memory. Two experiments showed that the more T2 performance exceeded that for T1, the more order reversals were made. Furthermore, precuing T1 led to a shift in performance benefits from T2 to T1 and to an equivalent reduction in order reversals. We conclude that it is not necessary to assume episodic integration to explain lag 1 sparing or the accompanying order reversals. (PsycINFO Dat
Keywords: attentional blink; order reversals; prior entry; working memory; visual attention; attentional performance; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Discrimination (Psychology); Female; Humans; Male; Memory; Short-Term; Pattern Recognition; Visual; Psychophysics; Reaction Time; Reversal Learning; Sensory Gating; Serial Learning; Young Adult; Eyeblink Reflex; Stimulus Change; Stimulus Parameters; Visual Attention; Attentional Blink; Short Term Memory

Acoustic Packaging and the Learning of Words - Schillingmann, Lars; Wagner, Petra; Munier, Christian; Wrede, Britta; Rohlfing, Katharina
Keywords: Prominence; Multimodal Action Segmentation; Feedback; Color Saliency; Human Robot Interaction

Direct parameter specification of an attention shift: Evidence from perceptual latency priming. - Scharlau, Ingrid; Ansorge, Ulrich (Vision Research)
In the direct parameter specification (DPS) mode of sensorimotor control, response parameters can be specified by stimuli that are not consciously perceived [Psychological Research/Psychologische Forschung 52 (1990) 207]. DPS is contingent on the current intentions. The invisible stimuli can be processed for the purposes of sensorimotor control only if they match the actual intentions, for example, share task-relevant features. The present experiments explore whether attentional capture by masked abrupt-onset stimuli is mediated via DPS. Participants judged which of two visual targets appeared first. Masked primes preceded one of the targets. The primes were either similar to the targets or not, in shape, or in color. Target-like (task-relevant), but not distractor-like (task-irrelevant), primes facilitated perceptual latencies of targets trailing at their positions. Thus, the latency effects resulted from DPS of an attention shift, rather than from bottom-up capture or from top-down
Keywords: direct parameter specification; DPS; attention shift; latency priming; sensorimotor control; stimuli; task-relevant features; visual targets; color; shape; latency effects; Adult; Attention; Discrimination (Psychology); Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Visual Perception; Attention; Perceptual Motor Processes; Response Latency; Stimulus Onset; Visual Stimulation; Form and Shape Perception; Sensory Adaptation